User-centered design of online learning communities - Λαμπροπούλου, Νίκη, 1966- (Information Science Publishing, 2007)
"This book is anchored in the concept that information technology empowers and enhances learners' capabilities adopting a learning summit on using the machine for the augmentation of human intellect for productivity, improvment, and innovation at individual, organizational,societal, national and global levels"